Axis II Personality Disorders Are Linked to an Adverse Course of Bipolar Disorder. Issue 6 (June 2018) - Post, Robert M.; McElroy, Susan; Kupka, Ralph; Suppes, Trisha; Hellemann, Gerhard; Nolen, Willem; Frye, Mark; Keck, Paul; Grunze, Heinz; Rowe, Michael
Abstract : Abstract: The relationship of personality disorder (PD) psychopathology to the course of bipolar disorder remains inadequately described. After giving informed consent, more than 782 outpatients with bipolar disorder rated themselves on the 99-item Personality Disorder Questionnaire, Version 4 (PDQ4) when depressed or euthymic. They also rated six poor prognosis factors (PPFs). The relationships of the PPFs to the total PDQ4 score were examined by a linear regression. Even after correcting for the higher PDQ4 scores observed when patients were suffering depression, the PDQ4 was significantly related to a history of child abuse, early age of onset, an anxiety disorder comorbidity, rapid cycling, and 20 or more previous episodes, but not substance abuse. The data suggest close relationships between the total burden of PD psychopathology and correlates of an adverse outcome of bipolar disorder. The nature of this of association and approaches to treatment of comorbid PD remain to be further explored.